EMPOWERING THE JUNIOR HIGH SCHOOL TEACHERS IN BUKITTINGGI TO OVERCOME THE PROBLEMS IN LEARNING CRAFTS - Wisdiarman Wisdiarman; Ariusmedi Ariusmedi; Erwin Erwin; Suib Awrus (Fakultas Bahasa dan Seni UNP, 2018)
Crafting in junior high school consists of some learning materials such as handcrafting, processing, engineering, and cultivating. The learning material that must be given junior high school students in Bukittinggi is crafting because it is appropriate with the conditions of the area that is close to the centers of handicrafts. In fact, the problem found from the observation was that the teachers generally (82,73%) are not from the art and craft education. The teachers who are from art or craft education will be easier to teach crafts than those who are not. Those who are not from art education got problems in the implementation of craft learning materials. It was happened because they did not master or did not have enough experience about it. Moreover, the junior high school teachers also lacked of learning strategies that are in line with the demands of the 2013 curriculum. As a result, the implementation of craft learning, especially craft materials, did not run well. The solution offered to solve the above-mentioned problems was the application of science and technology with several approaches; 1) designing, 2) counseling by presenting training material, 3) training in crafting and designing learning strategies, and 4) mentoring. The results of this activity were; 1) Most of junior high school teachers (77.77%) have mastered the craft materials given, especially makrame and woven crafts, 2) Most of them (88.88%) have mastered learning strategies that are in line with scientific approaches in the 2013 Curriculum. Keywords: Increasing teachers’ ability, craft learning, craft learning materials, learning strategies in 2013 curriculum